UV–Vis–IR spectral complex refractive indices and optical properties of brown carbon aerosol from biomass burning. (February 2018) - Sumlin, Benjamin J.; Heinson, Yuli W.; Shetty, Nishit; Pandey, Apoorva; Pattison, Robert S.; Baker, Stephen; Hao, Wei Min; Chakrabarty, Rajan K.
Highlights: Measured brown carbon aerosol optical properties and retrieved complex refractive indices ( m  =  n  +  i κ). Evaluated optical properties as functions of fuel moisture content, source depth, and geography. κ found to follow the Kramers–Kronig relationship for a damped harmonic oscillator. κ shows no functionality in moisture content, source depth or geography. Upon comparison to previous studies, κ shows a dependence on the fuel packing density. Abstract: Constraining the complex refractive indices, optical properties and size of brown carbon (BrC) aerosols is a vital endeavor for improving climate models and satellite retrieval algorithms. Smoldering wildfires are the largest source of primary BrC, and fuel parameters such as moisture content, source depth, geographic origin, and fuel packing density could influence the properties of the emitted aerosol. We measured in situ spectral (375–1047 nm) optical properties of BrC aerosols emitted from smoldering combustion of Boreal and Indonesian peatlands across a range of these fuel parameters. Inverse Lorenz–Mie algorithms used these optical measurements along with simultaneously measured particle size distributions to retrieve the aerosol complex refractive indices ( m = n + i κ). Our results show that the real part n is constrained between 1.5 and 1.7 with no obvious functionality in wavelength (λ), moisture content, source depth, or geographic origin. With increasing λ from 375 to 532 nm, κ decreased from 0.014 to 0.003, with corresponding increase in single scattering albedo (SSA) from 0.93 to 0.99. The spectral variability of κ follows the Kramers-Kronig dispersion relation for a damped harmonic oscillator. For λ ≥ 532 nm, both κ and SSA showed no spectral dependency. We discuss differences between this study and previous work. The imaginary part κ was sensitive to changes in FPD, and we hypothesize mechanisms that might help explain this observation.